2013
DOI: 10.3791/50648
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Spermatogenic Cell Types Using STA-PUT Velocity Sedimentation

Abstract: Mammalian spermatogenesis is a complex differentiation process that occurs in several stages in the seminiferous tubules of the testes. Currently, there is no reliable cell culture system allowing for spermatogenic differentiation in vitro, and most biological studies of spermatogenic cells require tissue harvest from animal models like the mouse and rat. Because the testis contains numerous cell types -both nonspermatogenic (Leydig, Sertoli, myeloid, and epithelial cells) and spermatogenic (spermatogonia, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 18 publications
0
59
0
4
Order By: Relevance
“…We hypothesized that depletion of H3K9me3, increased enrichment of H3K4me2, or both contribute to the inability to fully establish DNA methylation at hIC1. Spermatogenic cells were fractionated by the STA-PUT method, and chromatin was isolated from a round spermatid-enriched fraction (22). ChIP-qRT-PCR analyses in round spermatids revealed that hIC1 had fivefold greater enrichment of H3K4me2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that depletion of H3K9me3, increased enrichment of H3K4me2, or both contribute to the inability to fully establish DNA methylation at hIC1. Spermatogenic cells were fractionated by the STA-PUT method, and chromatin was isolated from a round spermatid-enriched fraction (22). ChIP-qRT-PCR analyses in round spermatids revealed that hIC1 had fivefold greater enrichment of H3K4me2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Round spermatid fractions of mouse spermatogenic cells were collected using STA-PUT in two independent replicates, and the purity of each fraction was verified as described previously (22,44). Each collection used both testes of 12 heterozygous (H19 hIC1/+ ) male mice.…”
mentioning
confidence: 99%
“…As mentioned above, Brd4 null heterozygous male mice show spermatogenic defects, suggesting that BRD4 may play a role in spermatogenesis (28,29). To investigate the expression pattern of BRD4 over the course of spermatogenesis, we analyzed protein levels in different cell types obtained by STA-PUT velocity sedimentation from mature mouse testes (35). By this method, we collected four cell populations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IF assay was performed with 8-m cryosections of testes from 10-week-old mice or cell suspensions obtained by the spermatogenic cell separation method described above (35). Testes were dissected and immediately placed in 4% paraformaldehyde (PFA; in phosphate-buffered saline [PBS]) or snap-frozen in liquid nitrogen.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation